Penerapan Aplikasi-Aplikasi Microsoft Office dan Google Docs dalam Upaya Peningkatan Media Pembelajaran di Madrasah Aliyah Negeri 5 Bireuen - Irvanizam, Irvanizam; Misbullah, Alim; Zulfan, Zulfan; Farsiah, Laina; Subianto, Muhammad (Universitas Syiah Kuala, 2023)
This community service activity aims to introduce Microsoft Office and Google Docs applications to teachers and students at Madrasah Aliyah Negeri (MAN) 5 Bireuen as an online teaching media in performing teaching and learning processes during the COVID-19 pandemic. This activity was carried out by a community service team of lecturers from the Department of Informatics, Universitas Syiah Kuala. The activity was held for three days from 2 until 4 April 2021 and consisted of two sessions. The first session introduced Microsoft Office applications for learning at the high school level. The second session demonstrates Google Docs applications for providing teaching materials. The activity participants were very enthusiastic about participating in this activity by asking lots of questions and being explained by the community service team. The result of this activity is that teachers find it very easy and quick to understand how to use these applications for their teaching and learning activities. They hope that online learning activities using the website-based Content Management System method will continue to be carried out as future works.